Diseño e implementación de alumbrado con bombillas tipo Led bajo los requisitos exigidos por RETILAP en la Casa Máquinas – Unidades Principales – Estación Vasconia- Cenit, Puerto Boyacá - Osorio González, Fernán David (Universidad Antonio Nariño, 2024)
This project is carried out with the design and execution of an improvement proposal with LED lighting in the area of the Vasconia station machine house, Cenit - Puerto Boyacá, in order to guarantee adequate illuminance levels for a work environment. safe and efficient, taking into account the technical lighting regulations (RETILAP).